Atmospheric dimethyl sulfide and its significant influence on the sea-to-air flux calculation over the Southern Ocean. (July 2020) - Zhang, Miming; Park, Ki-Tae; Yan, Jinpei; Park, Keyhong; Wu, Yanfang; Jang, Eunho; Gao, Wei; Tan, Guobin; Wang, Jianjun; Chen, Liqi
Highlights: Much stronger variabilities in atmospheric DMS were examined compared to those in seawater over the Southern Ocean. Wind speed and horizontal air mass convection can strongly impact the distribution of atmospheric DMS. DMS emission was strongly overestimated over the Southern Ocean. Abstract: Our understanding about the atmospheric dimethyl sulfide (DMS) and its influence to sea-to-air flux calculation in the Southern Ocean is still limited due to insufficient investigations. Herein, high-resolution shipboard underway simultaneous surface seawater and atmospheric DMS measurements were conducted in the Southern Ocean from February 23 to March 31, 2018. A larger variation of DMS levels was found in atmosphere compared with that in seawater. Remarkably, a large-scale area with high seawater and atmospheric DMS concentrations up to 27.9 nM and 3.92 ppbv, respectively, was investigated outside of Ross Sea sector. Atmospheric DMS levels were strongly impacted by wind speed and air mass convection. The relationship between atmospheric DMS and air mass exposure to oceanic chlorophyll varied greatly depending on the area of investigation. Some other regions with high DMS production capacity were examined as well beside those along the cruise tracks based on the results of positive correlations with high slopes and back trajectories. Moreover, significant uncertainty of sea-to-air DMS flux over the Southern Ocean could be caused by follows: (1) the selecting of different gas transfer coefficients; (2) the negative flux values calculated under high atmospheric DMS levels together with low seawater DMS concentrations; and (3) the greatly overestimated flux, approximately 47.1–76.9%, without considering the atmospheric DMS. This study highlights the urgent demand of high-resolution observations of atmospheric DMS over the Southern Ocean to estimate DMS emission with high accuracy.